Sustainable Homestead Farming for Better Food and Nutrition Security: A Success Story of Farida Begum from Bangladesh - Humaira Sadaf, Bushra; Haque, Abdul; Miajy, Abdullah; Ahmed, Sharif; Bhandari, Humnath (International Rice Research Institute, 2024)
This article highlights Mrs. Farida Begum’s success in improving food security, nutrition, and income through integrated year-round home-stead vegetable farming. Mrs. Farida Begum, a 45-year-old mother of three, lives in Shahbajpur, Rangpur Sadar, Rangpur District in northwestern Bangladesh with her family. Together, they manage a 3.5-acre main crop field, where they cultivate rice, maize, sugarcane, and mustard. Besides, the family has a 2.5 decimal homestead area next to the house. While her husband primarily manages the field crops, Mrs. Farida and her children have taken the lead in transforming their homestead garden into a thriving source of year-round vegetables and fruits, thanks to the CGIAR Initiative on the Sustainable Intensification of Mixed Farming Systems (SI-MFS) for its excellent support.